Anti-ulcerogenic activity of xanthanolide sesquiterpenes from Xanthium cavanillesii in rats - Favier, Laura Silvina (2005)
The preventive effect of natural xanthanolides as well as a series of synthetic derivatives on ulcer formation induced by absolute ethanol in rats was examined. Among the compounds tested, xanthatin gave the strongest protective activity. The inhibitory action exerted by this molecule on the lesions induced by 0.6N HCl and 0.2N NaOH was highly significant, reducing ulceration in the range of 58-96% at a dose from 12.5 to 100 mg/kg. These results appear to confirm that the presence of a non-hindered α,β-unsaturated carbonyl group seems to be an essential structural requirement for the gastric cytoprotective activity of these compounds. In order to explore this possibility, a theoretical conformational analysis was performed. We suggest that the mechanism of protection would involve, at least in part, a nucleophylic attack of the sulfhydryl group from the biological molecules present in the gastric mucosa to electrophylic carbons accessible in suitable Michael acceptors.